Prevalence and Factors Associated with Personal and Work-Related Burnout among Primary Health Care Physicians in Tabuk, Saudi Arabia - Hajira Saba Ishaq; Humaira Ayub; Shaima Hamid Albelawi; Mohammed Ahmad Altawili; Saada Shayeh Alenazi; Hamza Mohamed Ibrahim Omer; Mohammad Al Mamun (The Saudi Journal of Health Systems Research)
Introduction: Physician burnout is a growing concern worldwide, including in Arab nations. Physicians working in primary health care settings are increasingly experiencing it. The study aimed to assess the status and determinants of burnout among primary health care physicians in the Tabuk Region, Saudi Arabia. Methods: A cross-sectional study was carried out using a Google Form questionnaire, based on the Copenhagen Burnout Inventory. The questionnaire was distributed among primary health care physicians through the Ministry of Health’s email and social media channels. The responses were collected using a five-point Likert scale, and the overall mean scores for personal and work-related burnout were calculated. Data analysis was performed using SPSS 16.0 and OpenEpi Version 3.01. Results: A total of 92 primary health care physicians responded to the survey. The overall mean scores for personal and work-related burnout were 38.99 and 41.41, respectively. The most common response category for both types of burnout was “Sometimes” or “Somewhat” Physicians experienced personal burnout, characterized by emotional exhaustion (92.4%), feelings of being worn out (88%), tiredness (79.3%), and a sense of weakness and vulnerability to illness (69.6%). Similarly, they reported work-related burnout, manifested by feeling worn out after work (91.3%), feeling exhausted before work (83.7%), feeling burnt out by their work (82.6%), and feeling frustrated by their work (82.6%). Both personal and work-related burnout showed significant associations (p < 0.05) with age group, gender, years of experience, marital status, and professional category. Moreover, nationality, hours of work per week, and duty schedule were significantly associated with work-related burnout (p < 0.05). Conclusion: Physician burnout, both personal and work-related, is prevalent in primary health care settings in the Tabuk Region. It is significantly associated with various demographic and professional characteristics. Health care administrators and policymakers should develop and implement effective strategies to mitigate burnout and its detrimental effects on health care providers and the quality of care.